Marginal Productivity and the Macro-Economic Theories of Distribution: Comment on Samuelson and Modigliani - Kaldor, Nicholas (Review of Economic Studies, 1966)
Journal Article Marginal Productivity and the Macro-Economic Theories of Distribution: Comment on Samuelson and Modigliani Get access Nicholas Kaldor Nicholas Kaldor King's College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 4, October 1966, Pages 309–319, https://doi.org/10.2307/2974428 Published: 01 October 1966